EKSPLORASI BUDAYA DAN POTENSI WISATA BAHARI DI MUSEUM PUSAKA NIAS - Yurmanius Waruwu; Ferdinand Tharorogo Wau; Darius Halawa; Aluiwaauri Tafonao; Kristine Wau; Setia Murni Telaumbanua (Haga : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to optimize the role of the Nias Heritage Museum as a center for cultural preservation and as an educational medium in developing marine tourism potential based on local culture. The Nias Heritage Museum preserves various historical heritages and traditions of the Nias community, including maritime culture, which plays an important role in the lives of coastal communities. Through this activity, an exploration of maritime cultural values is conducted to enhance public understanding and encourage their utilization as an educational tourism attraction. The implementation methods include direct observation, interviews with museum managers and local communities, participatory discussions, and documentation of existing maritime cultural collections and narratives. In addition, socialization and educational activities are carried out to raise public awareness of the importance of preserving maritime culture and the opportunities for its development within the tourism sector. The results indicate that the Nias Heritage Museum has significant potential for the development of culture-based marine tourism, particularly through strengthening collection narratives, improving managerial capacity, and fostering active community involvement. This activity has a positive impact on increasing public awareness of the importance of maritime cultural preservation while also creating opportunities for local economic development. Therefore, this community service initiative is expected to support the development of sustainable tourism in Nias.